Alterações bioquímicas em bolsas de sangue total e de concentrado de hemacias de cães estocadas por 49 DIAS - Da Rosa Sobreira, Márcia Ferreira [UNESP]; Azenha, Eveline Simoes; Casale, Roberta Pinho; Silva, Bianca Mangueira; Costa, Bruna Garcia; Camplesi, Annelise Carla; Vieira, Manuela Cristina [UNESP] (My University, 2013)
The scope of this study was to evaluate biochemical characteristics of ten bags of whole blood and packed red cells of healthy dogs stored under refrigeration (4 + 2°C) for 49 days. The evaluation was conducted in seven times with an interval of seven days between each time and included the measurement of free hemoglobin and 2,3 - diphosphoglycerate (2,3-DPG). According to the results of the mean values of free hemoglobin increase incrementally during times of storage bags in both whole blood and in red blood cells, being more pronounced 35 days after its making. The 2,3-DPG decreases gradually during storage, especially after 21 days in bags of whole blood and 14 days in bags of PRBC. The viability of erythrocytes in blood bags total (CPDA-1) and red blood cells decreases with storage time, storage was indicated by a maximum period of 35 days. Financial support: Fapesp (proc. 2012/04007-7).
Biochemical alterations of canine whole blood and packed red cells storage in CPDA-1 solution for 49 days
Keywords: 2,3-DPG; Free hemoglobin; Hemotherapy; Injury storage